The complement fixation test in the identification of human rotavirus - Candeias, J. A. N.; Rácz, M. L.; Breviglieri, José Carlos; Rosenburg, Cornélio P. (Revista de Saúde Pública, 1980)
After eliminating the anticomplementarity of the fecal extracts, complement fixation was used to detect human rotavirus in the stools of 35 (28.7%) out of 122 one-to twelve-month-old children with acute gastroenteritis. Infection was nigher in the 6-to 12-month-old children.